2021
DOI: 10.1128/jcm.00609-21
|View full text |Cite
|
Sign up to set email alerts
|

False Immunological Detection of CTX-M Enzymes in Klebsiella oxytoca

Abstract: The global spread of extended-spectrum-β-lactamase (ESBL) is a matter of great concern given high morbidity and mortality associated with invasive infections.…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It is intriguing that no correlation was found between cross-reactivity and pairwise identity with CTX-M-2, which is their closest CTX-M member in phylogenetic analysis. In the case of OXY β-lactamases, it was previously hypothesized that residues of the Lys-Lys-Ser (KKS) triplet at Amber positions 101 to 103 was responsible for the cross-reactivity and explains why false-positive results occurred with the OXY-1 group but not the OXY-2 group variants [ 25 ]. Our results showed that several β-lactamases with amino acid triplets other than KKS at those positions also yielded false-positive results, including an OXY-2 variant and several other β-lactamases (FONA-8, -9, -11, -13 and SFO-1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing that no correlation was found between cross-reactivity and pairwise identity with CTX-M-2, which is their closest CTX-M member in phylogenetic analysis. In the case of OXY β-lactamases, it was previously hypothesized that residues of the Lys-Lys-Ser (KKS) triplet at Amber positions 101 to 103 was responsible for the cross-reactivity and explains why false-positive results occurred with the OXY-1 group but not the OXY-2 group variants [ 25 ]. Our results showed that several β-lactamases with amino acid triplets other than KKS at those positions also yielded false-positive results, including an OXY-2 variant and several other β-lactamases (FONA-8, -9, -11, -13 and SFO-1).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that cross reactivity is complex and might be influenced by protein folding and the level of β-lactamase expression. OXY and FONA are chromosomally-encoded ESBLs in K. oxytoca and S. fonticola , respectively, whereas SFO-1 is an uncommon plasmid-mediated ESBL that has been detected in members of Enterobacterales [ 25 , 26 , 27 ]. Since these are ESBL-producers anyway, the cross-reactions with CTX-M are of little clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…For CPE strains not suspected to produce an ESBL, the modified CDD test may be performed (only with class B CPE) for confirmation of suspected AmpC production. Furthermore, K. oxytoca CPE isolates suspected to produce an ESBL and/or AmpC may be subjected to the modified CDD test, since for these strains the CTX-M-MULTI test is unreliable due to production of an intrinsic OXY-1 β-lactamase, which may give rise to false-positive results ( 15 ). Strains of species producing an intrinsic AmpC may also be initially examined using the CTX-M-MULTI test when ESBL production is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Production of CTX-M-type ESBLs was confirmed with the CTX-M-MULTI (V2) lateral-flow immunoassay according to the manufacturer’s instructions (NG Biotech) ( 7 ). Due to known possible cross-reactivity of intrinsic OXY-1-type β-lactamases with monoclonal antibodies contained in the CTX-M-MULTI assay, this test was not performed with K. oxytoca isolates ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…In countries where the prevalence of other-than-CTX-M-type ESBL enzymes is important such as those from Asia, South America, or Middle East, the Rapid ESBL NP® offers the advantage to detect any kind of ESBL producers. In addition, one shall be aware that false detection of ESBL has been noted by using the NG CTX-M MULTI® assay for several K. oxytoca strains that possess specific naturally occurring ESBLs of OXY type [30]. All the tests evaluated are low cost and require no specialized equipment or personnel; further studies on cost-benefit analysis are needed however.…”
Section: Discussionmentioning
confidence: 99%